2006
DOI: 10.1186/1749-8104-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and orientation of retinal ganglion cells in vivo

Abstract: In the absence of external cues, neurons in vitro polarize by using intrinsic mechanisms. For example, cultured hippocampal neurons extend arbitrarily oriented neurites and then one of these, usually the one nearest the centrosome, begins to grow more quickly than the others. This neurite becomes the axon as it accumulates molecular components of the apical junctional complex. All the other neurites become dendrites. It is unclear, however, whether neurons in vivo, which differentiate within a polarized epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
142
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 221 publications
(153 citation statements)
references
References 45 publications
11
142
0
Order By: Relevance
“…The H2A-GFP transgene, for example, allows one not only to visualize cell nuclei but also to distinguish when cells undergo mitosis, and even to determine the orientation of mitotic spindles in the retinal neuroepithelium (Cui et al ., 2007; Pauls et al ., 2001). Similarly, GFP-centrin can be used to monitor the position of the centrosome in differentiating ganglion cells (Zolessi et al ., 2006), and GFP fused to a mitochondrial localization sequence can be applied to observe the distribution of mitochondria (Kim et al ., 2008). GFP fused to the 44 C-terminal amino acids of rod opsin is targeted to the photoreceptor outer segment and can be used as a specific marker of this structure (Perkins et al ., 2002).…”
Section: Analysis Of Wild-type and Mutant Visual Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The H2A-GFP transgene, for example, allows one not only to visualize cell nuclei but also to distinguish when cells undergo mitosis, and even to determine the orientation of mitotic spindles in the retinal neuroepithelium (Cui et al ., 2007; Pauls et al ., 2001). Similarly, GFP-centrin can be used to monitor the position of the centrosome in differentiating ganglion cells (Zolessi et al ., 2006), and GFP fused to a mitochondrial localization sequence can be applied to observe the distribution of mitochondria (Kim et al ., 2008). GFP fused to the 44 C-terminal amino acids of rod opsin is targeted to the photoreceptor outer segment and can be used as a specific marker of this structure (Perkins et al ., 2002).…”
Section: Analysis Of Wild-type and Mutant Visual Systemmentioning
confidence: 99%
“…GFP fused to the 44 C-terminal amino acids of rod opsin is targeted to the photoreceptor outer segment and can be used as a specific marker of this structure (Perkins et al ., 2002). FPs can also be applied to mark specific cell membrane domains: PAR-3/EGFP fusion, for example, labels the apical surface of retinal neuroepithelial cells (Zolessi et al ., 2006). …”
Section: Analysis Of Wild-type and Mutant Visual Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). 11,34,40 Remarkably, these structures are always located away from the site of axon outgrowth and close to the base of the forming dendrites. Prolonged erratic movements of the centrosome have been observed in these cells upon Laminin a1 knockdown, a treatment that also caused defects in neuronal polarization.…”
Section: Cilia In Neuronal Differentiationmentioning
confidence: 99%
“…In the zebrafish retina, where detaching retinal ganglion cells drag apical marker proteins at the tip or their apical processes, the same proportion of subapical cilia was observed before and after the initiation of neurogenesis. 11,34 Alternatively, an apical abscission mechanism has been described in chick neural tube. 35 The authors observed that detaching neurons actively left behind a small region of the apical process containing several apical complex proteins as well as the primary cilium (Fig.…”
Section: Cilia In Delaminating and Migrating Progenitors And Neuronsmentioning
confidence: 99%